2023
DOI: 10.3389/fcimb.2023.1220089
|View full text |Cite|
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans cytolethal distending toxin modulates host phagocytic function

Taewan J. Kim,
Bruce J. Shenker,
Andrew S. MacElroy
et al.

Abstract: Cytolethal distending toxins (Cdt) are a family of toxins produced by several human pathogens which infect mucocutaneous tissue and induce inflammatory disease. Human macrophages exposed to Aggregatibacter actinomycetemcomitans (Aa) Cdt respond through canonical and non-canonical inflammasome activation to stimulate cytokine release. The inflammatory response is dependent on PI3K signaling blockade via the toxin’s phosphatidylinositol-3,4,5-triphosphate (PIP3) phosphatase activity; converting PIP3 to phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…To date, we have demonstrated that Cdt is a tri-perditious toxin that can profoundly affect acquired and innate immune cells as well as epithelial barrier function [ 27 , 28 , 30 , 39 , 43 , 91 , 92 ]. We propose that Aa Cdt-induced OE senescence is a significant contributing factor to A. actinomycetemcomitans infection and the subsequent development of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, we have demonstrated that Cdt is a tri-perditious toxin that can profoundly affect acquired and innate immune cells as well as epithelial barrier function [ 27 , 28 , 30 , 39 , 43 , 91 , 92 ]. We propose that Aa Cdt-induced OE senescence is a significant contributing factor to A. actinomycetemcomitans infection and the subsequent development of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were permeabilized and blocked in 5% BSA and 0.2% Triton X-100 in PBS (PBST) at 37 • C for 1 h. Cells were then incubated with a 1:100 dilution of anti-ß-catenin antibody (Cell Signaling) diluted in blocking solution at 4 • C overnight, washed three times with PBST, incubated with donkey anti-rabbit Alexa Fluor 488 (1:1000; Invitrogen) and Hoechst 33258 (1:10,000; Invitrogen) at 37 • C for 1 h, washed and mounted in Prolong Gold Antifade reagent (P36930, Invitrogen). Confocal Z-stack images were acquired on a Nikon A1R laser scanning confocal microscope with a 60X (water) objective at 18 • C, and the data were analyzed using Nikon software (NIS Elements AR 5.30.03) [30].…”
Section: Analysis Of Epithelial Barrier Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly and expression of the plasmid containing the cdt genes encoding the holotoxin (pUCAacdtABChis) is described in prior studies [25]. The plasmid was engineered to incorporate the cdt genes under the regulation of the lac promoter and subsequently introduced into E. coli DH5α.…”
Section: Expression and Purification Of Cdt Cdtb Mutants And Cdt Holo...mentioning
confidence: 99%
“…After an overnight freezing step followed by thawing, the cells were subjected to sonication. The purification of the histidine-tagged peptide holotoxin was accomplished using nickel affinity chromatography, as described previously [25].…”
Section: Expression and Purification Of Cdt Cdtb Mutants And Cdt Holo...mentioning
confidence: 99%